2000
DOI: 10.1016/s0029-7844(00)00825-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of intramuscular nerves within the female striated urogenital sphincter muscle*1

Abstract: Remarkable variation in the quantity of intramuscular nerves was found. Women with sparse intramuscular nerves had fewer striated muscle cells. Intramuscular nerve density declined with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…Similar to our findings, prior urodynamic studies consistently report decreases in urethral closure pressures in continent women with advancing age(12, 13). Our urethral EMG data, which show MUP changes consistent with neuropathy not myopathy, support that the histologic findings of decreased muscle are likely secondary to neuromuscular decline rather than primary muscle pathology(14, 15). …”
Section: Discussionsupporting
confidence: 71%
“…Similar to our findings, prior urodynamic studies consistently report decreases in urethral closure pressures in continent women with advancing age(12, 13). Our urethral EMG data, which show MUP changes consistent with neuropathy not myopathy, support that the histologic findings of decreased muscle are likely secondary to neuromuscular decline rather than primary muscle pathology(14, 15). …”
Section: Discussionsupporting
confidence: 71%
“…They suggest that loss of muscle fibers with aging is consistent with the hypothesis that muscle loss is a result of neural injury but conclude that the way nerve injury would affect urethral function remains unclear. Our urethral EMG data, which show MUP changes consistent with neuropathy not myopathy, support that the histologic findings of decreased muscle are likely secondary to neuromuscular decline rather than primary muscle pathology [21, 22]. …”
Section: Discussionsupporting
confidence: 68%
“…Older women demonstrated decreased MUP recruitment as measured by decreasing numbers of turns and lower turns/amplitude ratio. This relationship between age and urethral function is consistent with urodynamic measures of urethral function, histologic studies, and clinical rates of stress incontinence [6, 1921]. Urodynamic studies consistently report decreases in urethral closure pressures in continent women with advancing age [19, 20].…”
Section: Discussionsupporting
confidence: 66%
“…Multiparous women also showed higher age, larger numbers of pregnancies, and a higher prevalence of prior miscarriages/abortions than did nulliparous women in our study, which might explain why multiparous women were more susceptible to UI and pelvic floor changes than nulliparous women. The previous studies reported that higher age leads to the loss of nerve function and a decrease in the total number of striated muscle fibers of the urethral sphincter at a rate of 2% per year and a gradual decline in the maximum urethral closure pressure of approximately 15% per decade ( Pandit et al, 2000 ; Wesnes & Lose, 2013 ). A previous study demonstrated that pregnancy itself has an effect on the pelvic floor ( Dietz et al, 2004 ); the mechanical and hormonal effects of pregnancy can lead to biomechanical, neurological, or neuromuscular changes to the pelvic floor and pelvic organ support ( South et al, 2009 ; Chen et al, 2005 ), which may lead to more obvious BN mobility and contribute to pelvic floor dysfunction.…”
Section: Discussionmentioning
confidence: 99%